1980
DOI: 10.1210/endo-107-5-1300
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lithium on Glucose and Tolbutamide-Induced Insulin Release and Glucose Tolerance in the Intact Rat*

Abstract: The effects of lithium on stimulus-induced insulin release and glucose tolerance were examined in intact, unanesthetized, and unrestrained rats with indwelling intravascular catheters. In the first study, a 150-mg iv glucose pulse was administered at 30 min after rapid iv injection of lithium carbonate (1 meq/kg) or vehicle. After the glucose pulse, mean serum glucose levels throughout the observation period were significantly greater in the lithium-treated rats than in the vehicle-treated (control) rats. Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 14 publications
2
9
1
Order By: Relevance
“…Lithium has been shown to inhibit glucose-stimulated insulin release in the rat after either in vitro or in vivo administration, leading to impairment of glucose tolerance (Anderson & Blackard, 1978;Shah & Pishdad, 1980). These effects of lithium can be counteracted by pretreatment of rats with dihydroergotamine (DHE), a non-selective a-adrenoceptor antagonist (Fontela et al, 1986;1987).…”
Section: Introductionmentioning
confidence: 99%
“…Lithium has been shown to inhibit glucose-stimulated insulin release in the rat after either in vitro or in vivo administration, leading to impairment of glucose tolerance (Anderson & Blackard, 1978;Shah & Pishdad, 1980). These effects of lithium can be counteracted by pretreatment of rats with dihydroergotamine (DHE), a non-selective a-adrenoceptor antagonist (Fontela et al, 1986;1987).…”
Section: Introductionmentioning
confidence: 99%
“…Glucose-stimulated insulin release is inhibited both in vivo and in vitro (Anderson & Blackard, 1978;Shah & Pishdad, 1980;Fontela et al, 1986;1987), and these effects appear to be mediated by central opiate and by neural and endocrine catecholamine pathways, the latter acting on the pancreatic P cell through its a2-adrenoceptors (Fontela et al, 1990; GarciaHermida et al, 1991). The aim of the present study was to investigate how this 'diabetogenic' effect of lithium in rats interacts with pre-existing diabetes mellitus, using streptozotocin-induced diabetes as the experimental model.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Studies in rats showed that intravenous infusion of lithium leads to hyperglycemia, increased levels of glucagon and lower insulin response induced by both glucose and tolbutamide (52). These effects can be attributed to the action of catecholamines in the sympathetic-adrenal system, pro-moting glycogenolysis, and to the direct effect of the drug on pancreatic alpha-2 and beta-adrenergic receptors, determining the reduction of insulin secretion and increased levels of glucagon (53).…”
Section: Glucose Metabolismmentioning
confidence: 99%